2011
DOI: 10.1017/s1049023x11006406
|View full text |Cite
|
Sign up to set email alerts
|

Value of Case Studies in Disaster Assessment?

Abstract: Case studies can be useful in assessing and learning lessons from emergency situations. In this paper, different uses for disaster case studies, are explored with identification of potential pitfalls that should be avoided. In addition, ways to improve the rigor and significance of case studies are suggested. Case studies can be used as examples or as a research tool. If conducted properly, they can provide robust and compelling results. It is argued that sharing a common guide to conducting and writing case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…14 However, disaster case studies have limitations, including in terms of external validity. 14 Further, it can be difficult to aggregate or compare evidence across single-storm studies because of differences in study methodology, and in meta-analyses publication bias often results in overestimation of associations. [15][16][17] Multi-year/multi-site studies can supplement case studies by providing: (1) a more precise and less biased estimate of the typical association between exposure and health risk [16][17][18] ; (2) evidence of consistency in health associations across multiple exposures 19 ; and (3) a clearer picture of heterogeneity-as well as factors that contribute to this heterogeneity-across associations observed for different events and at different sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, disaster case studies have limitations, including in terms of external validity. 14 Further, it can be difficult to aggregate or compare evidence across single-storm studies because of differences in study methodology, and in meta-analyses publication bias often results in overestimation of associations. [15][16][17] Multi-year/multi-site studies can supplement case studies by providing: (1) a more precise and less biased estimate of the typical association between exposure and health risk [16][17][18] ; (2) evidence of consistency in health associations across multiple exposures 19 ; and (3) a clearer picture of heterogeneity-as well as factors that contribute to this heterogeneity-across associations observed for different events and at different sites.…”
mentioning
confidence: 99%
“…Single-event case studies form an important component of disaster research, as such studies engage with complexity in the event and resonate across disciplines and among non-scientists. 14 However, disaster case studies have limitations, including in terms of external validity. 14 Further, it can be difficult to aggregate or compare evidence across single-storm studies because of differences in study methodology, and in meta-analyses publication bias often results in overestimation of associations.…”
mentioning
confidence: 99%
“…Following a guideline might help the inexperienced and make case studies more comparable. 45 If one were to write both a case report and fill out a template, researchers interviewed in this study suggested writing a case report to present the whole picture and then using the case report to fill out the template.…”
Section: Discussionmentioning
confidence: 99%
“…According to Glogowska (2011), qualitative method is used to study and examine phenomenon in a non-objective way because of similar elements from the researcher's attitude, belief and values. For this study, a descriptive case research design will be used to understand certain cases under observation (Grynszpan, Murray & Llosa, 2011). In this study, understanding the case study will be conducted through classroom observation: classroom observations will be conducted with all the three participants.…”
Section: Methodsmentioning
confidence: 99%